Associação entre excesso de peso corporal eperiodontite em adultos - Carneiro, Daline Oliveira (2019)
Obesity is considered a global epidemic that has reached individuals in their diferent socioeconomic and age groups. Its prevalence has had an impact on the morbidit and mortality rate, adding to problems of group of non-transmissible chronic diseases. The role of periodontitis as a factor associated with obesity has been highlighted. Periodontitis is a chronic disease that affects aproximately 20% of the Brazilian adult population and tends to be aggravated with advancing age. Studies that investigate excess weight as a risk factor for the occurrence of periodontitis are necessary in order to clarify the underlying biological mechanisms to this relationship.OBJECTIVE: To estimate the association of overweight and obesity with periodontitis in adults. METHOD: A cross-seccional study was carried on individuals with minimum age of 18 years attending Public Health Services in the municipality of Salvador-BA. Structured questionnaires were applied to obtain information on socioeconomic and demographic conditions, lifestyle and health care. Body Mass Index and Waist Circumference defined the diagnosis of excess weight (overweigth or obesity). Complete oral exam was performed by a dentist and clinical measures of probing depth, clinical attachment level, bleeding upon probing and tooth loss were registered. Diagnosis of periodontitis was obtained according to the severity of the disease (mild, moderate or severe) by two criteria adopted: (Criteria 01 and 2). New classification of Periodontitis from American Academic of Periodontology was applied too.For the evaluation of the main association, prevalence ratios with 95% confidence intervals were calculated by Poisson regression analysis. RESULTS: There was association between obesity as measured by abdominal circumference and periodontitis in women, even after adjusting for the confounding variables: age, smoking, years of schooling, diabetes and family income (Criteria 01 - RPadjusted: 2.02; 95% CI: 1.01-4.08; Criteria 2 - RPadjusted: 1.19; 95% CI: 1.01-1.40). CONCLUSIONS: Findings suggest a positive association between obesity and periodontitis in women and aged group 18-49 years-old. They also showed that women with high waist circumference are more likely to develop periodontitis, mainly in individuals with stage 3 of periodontitis. No association wasfound between overweight and periodontitis